2017
DOI: 10.11648/j.ajns.20170603.16
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Nursing Students’ and Clinical Instructors’ Perceptions of the Characteristics of an Effective Clinical Instructor at the Faculty of Nursing, Cairo University

Abstract: Learning in the clinical environment is an essential part of nursing education programs. Effective clinical teachingis crucial for the learning of nursing students in the clinical settings. It helps in preparing students for the work they will have to do as practicing nurses [1]. The study aimed to identify the undergraduate nursing students' and clinical instructors' perceptions of the characteristics of an effective clinical instructor at the Faculty of Nursing-Cairo University. A descriptive cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…The clinical nurse teachers on the other hand perceived that characteristics of an effective clinical nurse teacher are all necessary and should be possessed by them. The above result confirms the study of Banan & Elsharkawy (2017) at Cairo University finding that interpersonal relationships as a characteristic of a clinical teacher were most appreciated both by the nursing students and clinical instructors. [20] However, professional competence and personal traits are least appreciated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The clinical nurse teachers on the other hand perceived that characteristics of an effective clinical nurse teacher are all necessary and should be possessed by them. The above result confirms the study of Banan & Elsharkawy (2017) at Cairo University finding that interpersonal relationships as a characteristic of a clinical teacher were most appreciated both by the nursing students and clinical instructors. [20] However, professional competence and personal traits are least appreciated.…”
Section: Discussionsupporting
confidence: 86%
“…The above result confirms the study of Banan & Elsharkawy (2017) at Cairo University finding that interpersonal relationships as a characteristic of a clinical teacher were most appreciated both by the nursing students and clinical instructors. [20] However, professional competence and personal traits are least appreciated. Clinical teachers in these studies should have consistent awareness of their professional responsibilities since it has a boundless influence on the clinical learning processes for nursing students.…”
Section: Discussionsupporting
confidence: 86%
“…The results showed that the highest characteristic was "Professional Competence / Knowledge" and this agreed with the study stated that nursing competence was the clinical instructor characteristic that had the highest rating by clinical instructors [12]. Another study indicated that the categories of teaching ability and interpersonal relationships were the most valued characteristics and the least valued characteristics rated by clinical instructors were the categories of nursing competence rated by clinical instructors and this inconsistent with the current findings [10]. These differences could be attributed to differences in the research design, the educational needs and facilities and the nursing education curricula, particularly clinical teaching.…”
Section: Discussioncontrasting
confidence: 63%
“…Through reviewing literature, it was observed that most of the studies focused on the characteristics of the clinical instructor from the perspectives of nursing students, with few studies examining clinical instructors' opinions. Also, there were few studies exploring clinical instructors' perceptions about clinical training policies [10]. So, this study was done to assess clinical instructors' perceptions of the characteristics of an effective clinical instructor and their perceptions about effective clinical training policies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, A clinical nursing educator is a tool that assist students to integrate knowledge, skills and emotions required to provide patient care as the student transfers from teacher dependence to selfreliance. 21 Furthermore, regarding interpersonal relationship characteristics of nursing clinical educators, it was noticed that the participants provide positive perception. This finding in accordance with Moses (2017) who stated that knowledge and skill transition, which is at the focus education, based deeply on the interpersonal success of the educator.…”
Section: Discussionmentioning
confidence: 99%